The Impact of Technological Change in Process Design Decisions (Applied study in an organization) - الرحيم, اياد محمود; علي, شهد جبار (Journal of Economics and Administrative Sciences, 2025)
Abstract:     Due to the importance of technology and the accompanying changes of the environment affecting companies that use the technology mainly in their work, especially as most companies live in an unstable dynamic environment, which motivated the researchers to choose the International Company for smart card (Keycard) as a field of research and find ways to them to face Those changes.     The problem of the study was "limited attention to the components of technological change", which included research and development, innovation and information technology, which had an impact on the design decisions of the process (process selection, customer participation, flexibility of resources) Limited attention that being influencing company decisions related to process design.     The researchers used the descriptive analytical method and adopted the questionnaire as a tool in collecting data and information related to the study. It was distributed to a sample of 60 managers, officials and employees of the International Card Company. The SPSS.V.20 was used to analyze the data The results of the statistical analysis showed a correlation between the variables of the independent variable "technological change" and the variables of the dependent variable "process design decisions"     The most important conclusions of the study are the lack of interest of the company in some research and development activities, especially those related to the search for new ideas, which is reflected in the quality of services provided to customers as well as the company's neglect of the views of customers and feedback from them, which can be used to improve the characteristics and services of the company As appropriate for the customer